The effect of using an assistive device in learning the forehand and backhand strokes in tennis for ages (12-15) - حسيب, م. م حسن رائد (Sulaimani Journal for Humanities, 2026)
The study aimed to manufacture an aid device for learning the forehand and backhand strokes in tennis. It also aimed to identify the effect of the aid device on learning the forehand and backhand strokes. The researcher hypothesized that there would be statistically significant differences between the post-tests of the experimental and control groups in learning to perform the forehand and backhand strokes. The research methodology employed an experimental approach with two groups, experimental and control, using pre- and post-tests. The research sample consisted of beginners aged (12-15) years at Al-Jadriya Tennis Academy. The sample included (16) players who were randomly divided into two equal groups, experimental and control, with (6) players in each group, after excluding (4) players due to their non-compliance with the training sessions. The researcher concluded that using the aid device for exercises contributed to learning the forehand and backhand stroke skills. Furthermore, the continuous and varied repetition of exercises using the aid device increased the players' motivation towards better development in their skill performance.
Keywords: Tennis assistance device; age groups in tennis; forehand and backhand strokes in tennis